Short research article: COVID‐19 and its impact on child and youth mental health service demand in the community and emergency department. Issue 1 (15th August 2022) - Tedja, Amy M.; Shanmugam, Meenakshi S.; Stathis, Stephen; Middeldorp, Christel M.
Abstract : Background: To explore changes in child and youth mental health service (CYMHS) demand in Brisbane, Australia, following the COVID pandemic. Methods: The number of monthly presentations and referrals to respectively the emergency department (ED) and community CYMHS were compared among 2018, 2019 and 2020. Results: The study shows a marked increase in referrals to ED starting from July and in the community from May 2020. In the population referred to as community teams, the proportions of Indigenous children and those from lower socio‐economic areas decreased. Conclusions: The COVID‐19 pandemic has aggravated the supply and demand disparity in CYMHS, with the largest effect on the most vulnerable families.